LAS GRAPTOFAUNAS DE LA FORMACIÓN LOS SOMBREROS, ORDOVÍCICO INFERIOR, DE LA VERTIENTE ORIENTAL DE LA SIERRA DEL TONTAL, PRECORDILLERA DE SAN JUAN (Ameghiniana, 2013)
GRAPTOLITES FROM THE Los SOMBREROS FORMATION, LOWER ORDOVICIAN IN THE EASTERN SLOPE OF THE TONTAL HILL, PRECORDILLERA FOLD BELT OF SAN JUAN. - An early Ordovician sequence made up by gray limestones and black shales, approximately 1.000 m thick, cropping out in the central Precordillera fold belt (San Juan Province) has be en studied. Structural analysis shows that the sequence is part of a tectonic wedge; low and high angle faults separate it at the base and the top from Upper Devonian-Ordovician rocks. Three graptolitic faunas were díscovered in the lower part of the sequence: the first one is composed by Dictyonema sp., the second one by Callograptus cf. salteri Hall and the third one by Tetragraptus quadribrachiatus (Hall), Tetragraptus amii Elles & Wood, Tetragraptus cf. fruticosus (Hall), Tetragraptus? sp., Phyllograptus anna Hall and Didymograptus sp. The fossil-bearing beds constitute 35 m of the whole sedimentary sequence; the two first graptolitic associatíons are assigned to the Tremadocian and the last one to the Arenigian.